Advances in Communication, Signal Processing, VLSI, and Embedded Systems Select Proceedings of VSPICE 2019 - Kalya, Shubhakar; Kulkarni, Muralidhar; Shivaprakasha, K.S.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book comprises selected peer-reviewed papers from the International Conference on VLSI, Signal Processing, Power Systems, Illumination and Lighting Control, Communication and Embedded Systems (VSPICE-2019). The contents are divided into five broad topics - VLSI and embedded systems, signal processing, power systems, illumination and control, and communication and networking. The book focuses on the latest innovations, trends, and challenges encountered in the different areas of electronics and communication, and electrical engineering. It also offers potential solutions and provides an insight into various emerging areas such as image fusion, bio-sensors, and underwater sensor networks. This book can prove to be useful for academics and professionals interested in the various sub-fields of electronics and communication engineering.
Keywords: Electronic circuits; Signal processing; Image processing; Speech processing systems; Electrical engineering; Wireless communication systems; Mobile communication systems; Control engineering; Robotics; Mechatronics; Power electronics; Circuits and Systems; Signal, Image and Speech Processing; Communications Engineering, Networks; Wireless and Mobile Communication; Control, Robotics, Mechatronics; Power Electronics, Electrical Machines and Networks